SCIENTIFIC BOOK WRITING USING LYX A FRONT-END OF LATEX - Waluyo Adi Siswanto (Penerbit UTHM, 2011)
This book will guide you to use LyX which has a powerful LaTeX in the background. You just need to follow the Seven Steps, starting from Understanding LyX Environment, Document Preparation, Writing the Frontmatter, Writing the Mainmatter, Writing the Backmatter, Working with LaTeX Packages, and Printing the Manuscript. All scientific aspects of writing, such as Images, Tables, Mathematical Equations, BibTex database, and Index Preparation are all disscussed in detail. LyX will help you to prepare your scientific books.